The Influence of Television Watching Intensity on The Students’ Learning Interest - Patimah Patimah; Yaya Kiswaya (UIN Siber Syekh Nurjati Cirebon, 2019)
AbstractThis research is based on the low of students’ interest in learning. This is because they spend more time to watch television than to learn. This study aims to examine the effect of TV watching intensity on the students’ learning interest. This study uses quantitative methods with correlational design. Data are collected through questionnaire and observation. Meanwhile, the data analysis technique used was the regression test analysis. The results of the study show that the intensity of TV watching is 78% with high criterion and student learning interest is 89% with a high criterion. Based on the results of the regression test, it was found that the significant value is 0,000. Because the significant value is smaller than 0.05 and t count (4.817) is bigger than t table (2.052), Ho is rejected, meaning that the intensity of TV watching shows has a significant effect on the students' learning interest. Therefore, parents should be able to limit their time watching television to their children so that children's learning interest does not decrease.Keywords: students’ learning interest, television, watching intensity. AbstrakPenelitian ini dilatar belakangi oleh rendahnya minat belajar siswa. Hal ini karena mereka lebih banyak menghabiskan waktu untuk menonton televisi dibandingkan dengan belajar. Penelitian ini bertujuan untuk meneliti tentang pengaruh intensitas menonton televisi terhadap minat belajar siswa. Penelitian ini menggunakan metode kuantitatif dengan desain korelasional. Teknik pengumpulan data menggunakan angket dan observasi. Sementara itu, teknik analisis data yang digunakan adalah analisis uji regresi. Hasil penelitian ini menunjukkan bahwa intensitas menonton tayangan televisi sebesar 78% dengan kriteria tinggi dan minat belajar siswa sebesar 89% dengan kriteria tinggi. Berdasarkan hasil uji regresi diperoleh bahwa signifikansinya sebesar 0,000. Karena nilai signifikansinya lebih kecil dari 0,05 dan t hitung (4,817) lebih besar dari t tabel (2,052) maka Ho ditolak, artinya bahwa intensitas menonton tayangan televisi berpengaruh signifikan terhadap minat belajar siswa. Oleh karena itu, hendaknya orang tua dapat membatasi waktu menonton televisi kepada anak-anaknya agar minat belajar anak tidak menurun.Kata kunci: intensitas menonton, minat belajar siswa, televisi.